“Antifungal Stewardship” A Pertinent Exigency in Mycobial Treatment - Priyanka Debta; Santosh Kumar Swain; Ekagrata Mishra; Fakir Mohan Debta; Gargi Sarode; Mahesh Chandra Sahu (Indian Journal of Forensic Medicine & Toxicology, 2021)
“Stewardship” is an ethic that exemplifies the conscientious, and sustainable forethought with themanagement of resources. Antifungal stewardship” is evidence-based interventions for judiciousantifungal usage in healthcare setup, to get the best clinical outcomes and minimize adverse events andselective exhaustive pressures. This review briefly catalogues the seven core elements and supplementaryrecommendations by Mycoses Study Group Education and Research Consortium. Appraisal of AFS requiresa set of metrics which have been categorized into quantitative metrics, quality metrics, patient outcome andmicrobiological metrics and performance metrics or outcome measures. The four domains about barriersconcerning antimicrobial stewardship programs which include “outer setting”, “inner setting”, “individualsinvolved” and “the intervention”, have also been elucidated. At the present scenario, fungal infections areincreasing especially in immunocompromised and cancer patients thus financial strain imposed by these onhealth care is expected to escalate over time as the populace of individuals at risk augment. AFS comes tothe rescue to promote a wholesome utilization of currently available antifungal drugs to stem the tide of theemergence of resistance and morbidity of invasive disease.